Green preparation of debranched starch nanoparticles with different crystalline structures by electrostatic spraying. (June 2022) - Lin, Qianzhu; Liu, Yadi; Zhou, Liyang; Ji, Na; Xiong, Liu; Sun, Qingjie
Abstract: The aim of this study was to develop a simple and green method to prepare debranched starch nanoparticles (DSNPs) by electrostatic spray. Debranched starch obtained by hydrolyzing waxy corn starch was gelatinized and sprayed into an alcohol tank by electrostatic spray. The physical and chemical properties, such as particle size and morphology, of the DSNPs were systematically studied by dynamic light scattering, transmission electron microscopy, and X-ray diffraction. The DSNPs had diameters between 243 and 337 nm and good dispersion. The DSNP obtained in 60%, 80%, and absolute ethanol showed A-type crystalline, A + V-type crystalline, and amorphous structures, respectively. This simple method for preparation of starch nanoparticles with different crystalline structures has potential applications in different fields, including food, biomedicine, and agriculture. Graphical abstract: Image 1 Highlights: Debranched starch nanoparticles (DSNPs) was prepared by electrostatic spraying. The DSNPs had diameters between 243 and 337 nm with good monodispersity. DSNPs showed A-type crystalline, A + V-type crystalline, and amorphous structures. DSNPs with different structures will expand the application in different fields.